Perberdayaan Santri Melalui Pendidikan Kecakapan Hidup: (Life Skills) (Studi di Pondok Pesantren Darul A’mal Kota Metro) - Umam, Aguswan Khotibul (Tarbawiyah Jurnal Ilmiah Pendidikan, 2017)
Pesantren’s roles include providing life skill and internalizing Islamic principles in real life contexts. This research was focused on the empowerment of students’ life skill: personal skill,thinking skill, social skill, academic skill, and vocational skill at Pondok Pesantren Darul A’mal Metro Lampung. The students were trained on life skills through several trainings: reciting Islamic classical book,computer and IT, fahmil Qur’an, tilwatil Qur’an, public speaking skills, calligraphy, tahkfid nadzom, hadroh, syaril Qur’an; and the students also have opportunity to follow shalawat singing training and pencak silat sport such as Persaudaraan Setia Hati and Pagar Nusa. In order to succeed these programs, all stakeholders should cooperate to develop students’ life skills according to teaching vision and mission of the Pondok Pesantren.